Aberrant Gut Microbiome Contributes to Barrier Dysfunction, Inflammation, and Local Immune Responses in IgA Nephropathy - Yuyan Tang; Yong Xiao; Haidong He; Yifan Zhu; Weiqian Sun; Ping Hu; Xudong Xu; Zhen Liu; Zhaowei Yan; Minggang Wei (Karger Publishers, 2023)
Introduction: Numerous research works have shown that serum Gal-deficient (Gd) IgA1 levels are increased in IgA nephropathy (IgAN) patients and these levels are a dangerous risk factor for IgAN. A relationship between the gut microbiota and IgAN has been reported. Whether the gut microbiota participates in the pathogenesis of IgAN was still controversial. Methods: We evaluated changes in the gut flora and the levels of Gd-IgA1 in IgAN patients and healthy controls (HCs). We investigated the Gd-IgA1 levels in both blood and urine specimens. C57BL/6 mice were given a broad-spectrum antibiotic cocktail to deplete the endogenous gut flora. We established a model of IgAN in pseudosterile mice and investigated the expression of the markers of intestinal permeability, inflammation, and local immune responses. Results: Studies have shown that the levels of certain gut flora differ between IgAN patients and HCs. Moreover, elevated Gd-IgA1 levels were found in both the serum and urine. Interestingly, Coprococcus, Dorea, Bifidobacterium, Blautia, and Lactococcus, selected from 10 candidate biomarkers to predict risk in IgAN patients according to random forest analysis, were inversely associated with urinary Gd-IgA1 levels. Notably, the urine level of Gd-IgA1 could best distinguish IgAN patients from HCs. Additionally, the degree of kidney damage in pseudosterile mice with IgAN was more severe than that in mice with IgAN. Furthermore, the markers of intestinal permeability were significantly elevated in pseudosterile IgAN mice. Moreover, the inflammation responses (TLR4, MyD88, and NF-κB in intestinal and renal tissues; TNF-α and IL-6 in serum) and local immune responses (BAFF and APRIL in intestinal tissue) were upregulated in pseudosterile IgAN mice. Conclusions: The urine Gd-IgA1 level may be as a biomarker for the early screening of potential IgAN, and gut microbiota dysbiosis was demonstrated in IgAN, which might involve the dysfunction of the mucosal barrier, inflammation, and local immune responses.